Pengaruh Teknik 3M (Mengamati, Meniru dan Menambahi) Terhadap Kemampuan Menulis Teks Berita pada Siswa - Riska Riska; Supriadi Supriadi; Rahma Ashari Hamzah; Syarifah Nur Fajrin; Nur Afni (STKIP Andi Matappa Pangkep, 2023)
This study aims to determine the effect of 3M techniques (Observing, Imitating, and Adding) on the Ability to Write News Texts in Class VIII Students, to find out the description of the implementation of learning using 3M techniques, to find out the description of the application of 3M techniques in improving the ability to write news texts of class VIII students. The type of this research is experimental research. The research design used, namely The One Group Pretest-Posttest Design which is one type of Pre-experimental in experimental research. The results of the study are the implementation of learning using the 3M technique has not been completed as evidenced by the level of completeness of only 15% complete, the description of the application of the 3M technique (Observing, Imitating, and Adding) in improving the ability to write news texts in class VIII students is proven to be able to improve the ability of students with as many as 14 students with a percentage of 42% have reached completeness, hypothesis testing in this study there is or there is an influence of the 3M technique (Observing, Imitating, and Adding) on the Ability to Write News Texts in Class VIII Students proved significant.